2014
DOI: 10.1016/j.ttbdis.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity associated with low prevalence of Anaplasma marginale in water buffaloes in Marajó Island, Brazil

Abstract: 26The rickettsia Anaplasma marginale is the etiologic agent of bovine anaplasmosis, an 27 important tick-borne disease affecting cattle in tropical and subtropical regions of the 28 world. In endemic regions, the genetic diversity of this pathogen is usually related to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…In the comparative analysis of the snPCR result for msp5 gene among splenectomized animals, cattle presented a significantly higher average frequency of infection than buffaloes. Other studies also reported that buffaloes had lower values (Silva et al 2014a(Silva et al , 2014b compared to the observed in cattle (Bacanelli et al 2014). A splenectomized buffalo was positive only 60 days after inoculation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the comparative analysis of the snPCR result for msp5 gene among splenectomized animals, cattle presented a significantly higher average frequency of infection than buffaloes. Other studies also reported that buffaloes had lower values (Silva et al 2014a(Silva et al , 2014b compared to the observed in cattle (Bacanelli et al 2014). A splenectomized buffalo was positive only 60 days after inoculation.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the confirmed presence of this rickettsia in buffalo herds (Silva et al 2014a(Silva et al , 2014b(Silva et al , 2014c(Silva et al , 2015, there is little knowledge about the development of anaplasmosis in this species. Furthermore, there is no research that simultaneously evaluates the pathogenicity of A. marginale in cattle and buffaloes and compares the effects of the disease between the two species.…”
Section: Introductionmentioning
confidence: 99%
“…A fibra em detergente neutro e fibra em detergente ácido seguiram o método sequencial, descrito por Van Soest et al (1991). As determinações de proteína bruta foram efetuadas pelo método Kjeldahl (AOAC, 2005).…”
Section: Methodsunclassified
“…Observou-se que para cada 1% de acréscimo de gordura na dieta houve redução de até 6% na produção de CH 4 .kg -1 de matéria seca consumida (Abdalla et al, 2008). Na região Norte se concentram aproximadamente 900 mil cabeças de búfalos, ou 66% do efetivo nacional, especialmente na Ilha do Marajó, estado do Pará, onde é fonte primária de carne, leite e couro, além de ser animal símbolo da cultural regional (Silva et al, 2014;IBGE, 2017a). O dendezeiro está entre as oleaginosas tropicais de maior rendimento e potencial na obtenção de óleo, e para cada 100 toneladas de cachos processados são obtidas três toneladas da torta (Furlan Junior et al, 2006).…”
Section: Introductionunclassified
“…While the organisms in these clusters may also be antigenically related, studies similar to those done for influenza virus (Smith et al, 2004) are needed to establish this correlation. The bootstrap values are frequently higher than 60% (Silva et al, 2014a;Pohl et al, 2013) but may drop below 50% in many branches (Silva et al, 2014b). Nonetheless, the topology of the tree may identify clusters that are more highly conserved than others (Silva et al, 2014b;Pohl et al, 2013).…”
Section: Msp1a and Molecular Taxonomy Of A Marginalementioning
confidence: 99%